The Effect of Arabic Gum on Gentamicin Nephrotoxicity in Mice: A Pathological Study - Liqaa Alhyali; Firas Abed; Entisar AL-Kenanny (Medicinski glasnik, 2025)
Aim: To investigate the effect of Arabic gum on gentamycin nephrotoxicity in mice kidney. Methods: Forty (40) mice were divided into five groups, eight mice in each. Group one (G1) stands for the negative control group. The second one (G2) was injected with gentamycin only, while the third one (G3) was given an Arabic gum orally 10g/kg. The 4th group (G4) was injected with gentamycin for 8 days, and then followed by Arabic gum orally for 8 days. The fifth group (G5) was injected with gentamycin plus oral administration of Arabic gum at the same time. A scoring system (+1-+4) was used to grade the histological features in the kidneys. Results: The results revealed a significant increase in body weight in G3 group only; this group presented a significant decrease in the level of both urea and creatinine. Group G2 showed a marked elevation in both serum urea and creatinine. Acute tubular necrosis (+4), in both G2 and G5. In G3, kidney sections presented mild cell swelling of the tubular epithelium in addition to the normal architectures (score +1), while G4 sections revealed tubular hyalin cast, expansion of glomerular tufts. Conclusion: The research indicates that gentamycin leads to kidney damage in mice. Arabic gum could be a treatment option although additional studies are required to determine the best dosing and timing, for optimal effectiveness.
Keywords: creatinine; gentamycin; kidney; nephritis; urea